Blood Flow Imaging in Transesophageal Echocardiography during Atrial Septal Defect Closure: A Comparison with the Current References. Issue 1 (5th April 2014) - Nyrnes, Siri Ann; Løvstakken, Lasse; Døhlen, Gaute; Skogvoll, Eirik; Torp, Hans; Skjærpe, Terje; Norgård, Gunnar; Samstad, Stein; Graven, Torbjørn; Haugen, Bjørn Olav
<x xml:space="preserve">Abstract</x> Background Flow visualization before transcatheter atrial septal defect (ASD) closure is essential to identify the number and size of ASDs and to map the pulmonary veins (PV). Previous reports have shown improved visualization of ASD and PV using blood flow imaging (BFI), which supplements color Doppler imaging (CDI) with angle‐independent information of flow direction. In this study, we compared transesophageal BFI with the current references in ASD sizing (balloon stretched diameter, BSD) and PV imaging (pulmonary angiography). Methods In this prospective study, 28 children were examined with transesophageal echocardiography (TEE) including BFI of the secundum ASD and the PV before interventional ASD closure. The maximum ASD diameter measured with BFI by 4 observers was compared to the corresponding BSD and CDI measurements. The repeatability of the BFI measurements was calculated as the residual standard deviation. BFI of the PV was compared to PV angiography. Results The mean maximum diameter measured by BFI was 12.1 mm (±SD 2.4 mm). The corresponding BSD and CDI measurements were 15.9 mm (±SD 3.0 mm) and 11.8 mm (±SD 2.5 mm), respectively. The residual standard deviation was 1.2 mm. Compared to PV angiography, the sensitivity of BFI in detecting the correct entry of the PV was 0.96 (95% CI: 0.82–1.0). Conclusion Transesohageal echocardiography with BFI of the PV agreed well with pulmonary angiography. BFI had lower estimates for ASD size than BSD, but with acceptable 95% limits of agreement. The repeatability of the BFI measurements was close to the inherent ultrasound measurement error.